Effect of stress during different durations of dystocia on. various blood indices in buffaloes - DHINDSA, S S; GANDOTRA, V K; PRABHAKAR, S (The Indian Journal of Animal Reproduction, 2023)
Thirty three dystocia affected buffaloes were divided into four groups with labour pains less than 12 hours (group A; n =07), 12-24 hours (group B; n = 12), 24-36 hours (group C; n = 06) and more than 36 hours (group D; n = 08) to assess the degree ofsress with relation to different duration of dystocia. Plasma cortisol concentrations (3 .24-30.77 μg/dl) increased with duration ofonset of labour pains. Histamine concentration, total leukocytic count and neutrophils increased significantly (P < 0.01) from initialvalues of 460.08 μmol/1, 6.74x 103/cumm and 55.14 per cent, respectively, in group A to 602.14 μrnol/1, 9.90 x 10' cumm and 59.87per cent, respectively, in group D. Lymphocytes (36.62%) were non-significantly lower in group D as compared to other groups. Itis thus, concluded that increased concentrations of cortisol and histamine with alterations in otal leukocytic, neutrophilic andlymphocytic counts. indicated higher degree of stress in protracted cases of dystocia.
Keywords: Buffalo; cortisol; dystocia; histamine; stress